2014
DOI: 10.1017/s0266462314000683
|View full text |Cite
|
Sign up to set email alerts
|

Hta and Its Legal Issues: A Framework for Identifying Legal Issues in Health Technology Assessment

Abstract: The article underlines the importance of in-depth discussion about the role of law in HTA. It provides a structured overview of the legal issues in HTA and suggests a development of more concrete instruments toward a standardized legal technology assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Aware, however, that the term is often abbreviated to 'legal tech', I decided to extend my search to be certain that the analysis of sources was comprehensive (Lodhi, 2016). 14 Importantly, the review procedure confirmed that either of the verbal categories generated different results; hence, the assumption made was justified methodologically.…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…Aware, however, that the term is often abbreviated to 'legal tech', I decided to extend my search to be certain that the analysis of sources was comprehensive (Lodhi, 2016). 14 Importantly, the review procedure confirmed that either of the verbal categories generated different results; hence, the assumption made was justified methodologically.…”
Section: Methodsmentioning
confidence: 69%
“…Two each were published in Family Law Quarterly ([09], [10]), Legal Information Management ([02], [21]), Artificial Intelligence and Law ( [30], [31]), American Journal of Trial Advocacy ( [44], [46]), International Review of Law, Computers & Technology [35], [58]), University of Ottawa Press ( [60], [61]), and Indiana Journal of Global Legal Studies ( [15], [63]). The remaining journals included one text each on a given topic: Journal of Advanced Research in Law and Economics [03], The Journal of Equipment Lease Financing [04], Future Internet [05], Technology Innovation Management Review [07], Iowa Law Review [11], International Journal of Technology Assessment in Health Care [14], Union of Jurists of Romanis Law Review [16], Systemic Practice and Action Research [18], Revista Direito GV [20], Northwestern University Law Review [22], Journal of Nursing Law [23], The Entrepreneurial Executive [24], Texas Law Review [26], Journal of Digital Asset Management [27], Information Systems Frontiers [28], Journal of Financial Service Professionals [29], Federal Communications Law Journal [33], International review of Law, Computers & Technology [35], IT Professional [36], International Financial Law Review [37], Daedalus [38], IEEE Transactions on Software Engineering [39], Journal of East Asia and International Law [40], Croatian International Relations Review [41], International Tax Review [42], University of Toronto Law Journal [43]…”
Section: Bibliometric Analysis Focused On the Selection Of The Journal Research Questions And Abstractmentioning
confidence: 99%
“…There is no standardized approach for incorporating legal aspects [ 18 ]. Therefore, we will further specify the data extraction for legal aspects after the literature screening.…”
Section: Methodsmentioning
confidence: 99%
“…7 The most likely reason is that it is very problematic to test ethical implications of single technologies empirically as ethics reports to more general issues. 8 Roughly the same holds for legal aspects, 9 although they have been much less analysed in the literature. In practice, health technology assessment has always been much more narrowly defined in Europe, 10 and the main outcomes have been relative effectiveness and cost effectiveness analyses.…”
Section: Health Technology Assessment From Theory To Practicementioning
confidence: 99%